Colorectal cancer in Lynch syndrome families: consequences of gene germline mutations and the gut microbiota - Xuexin Wang; Zhijun Zheng; Dongliang Yu; Xiaojue Qiu; Ting Yang; Ruoran Li; Jing Liu; Xin Wang; Peng Jin; Jianqiu Sheng; Nan Qin; Na Li; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Lynch syndrome (LS)-associated colorectal cancer (CRC) always ascribes to pathogenic germline mutations in mismatch repair (MMR) genes. However, the penetrance of CRC varies among those with the same MMR gene mutation. Thus, we hypothesized that the gut microbiota is also involved in CRC development in LS families. Methods This prospective, observational study was performed from December 2020 to March 2023. We enrolled 72 individuals from 9 LS families across six provinces in China and employed 16S rRNA gene amplicon sequencing to analyze the fecal microbiota components among LS-related CRC patients (AS group), their spouses (BS group), mutation carriers without CRC (CS group), and non-mutation carriers (DS group) using alpha and beta diversity indices. Results There were no apparent differences in age or gender among the four groups. Alpha and beta diversity indices exhibited no significant differences between the AS and BS groups, verifying the role of germline mutations in the occurrence of CRC in LS families. Beta diversity analysis exhibited significant differences between the AS and CS groups, revealing the importance of the gut microbiota for the occurrence of CRC in LS families. A greater difference (both alpha and beta diversity indices) was shown between the AS and DS groups, demonstrating the combined impact of the gut microbiota and genetic germline mutations on the occurrence of CRC in LS families. Compared with those in the CS and DS groups, we identified ten microbial genera enriched in the AS group, and one genus (Bacteroides) decreased in the AS group. Among the elevated genera in the AS group, Agathobacter, Coprococcus and Prevotellaceae_NK3B31_group were butyrate-producing genera. Conclusion This study found the development of CRC in the LS families can be attributed to the combined effects of gene germline mutations as well as the gut microbiota and provided novel insights into the prevention and treatment of CRC in the LS families.